2020
DOI: 10.13057/biodiv/d210408
|View full text |Cite
|
Sign up to set email alerts
|

Ant and termite diversity in Indonesian oil palm plantation: Investigating the effect of natural habitat existence

Abstract: Abstract. Rizali A, Karindah S, Windari A, Rahardjo BT, Nurindah, Sahari B. 2020. Ant and termite diversity in Indonesian oil palm plantation: Investigating the effect of natural habitat existence. Biodiversitas 21: 1326-1331. Natural habitat existence in oil palm plantation has high conservation value and plays an important role in maintaining biodiversity. However, different taxa may have different responses to the presence of natural habitats. This research was aimed to investigate the effect of natural hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In addition, natural habitats have no effect on ants in the coffee agroforestry system. The previous study also found the same pattern that area and patch number of agricultural lands are more affected by insect diversity than natural habitats (e.g., Ulina et al 2019;Rizali et al 2020).…”
Section: Effect Of Habitat Condition and Landscape Composition On Ant...supporting
confidence: 58%
See 1 more Smart Citation
“…In addition, natural habitats have no effect on ants in the coffee agroforestry system. The previous study also found the same pattern that area and patch number of agricultural lands are more affected by insect diversity than natural habitats (e.g., Ulina et al 2019;Rizali et al 2020).…”
Section: Effect Of Habitat Condition and Landscape Composition On Ant...supporting
confidence: 58%
“…Ants are very sensitive to environmental change. Agriculture intensification, human disturbance, and land conversion are known to affect ant diversity (Solar et al 2016;Rizali et al 2020;Santos et al 2021). Because of their sensitive and rapid responses, ants can become good indicators of change in the environment (Tiede et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results of research on peat-lands with palm stands from a young age to old reported that 15 ant species were found (Darmi et al 2015). Rizali et al (2020) found 7 to 22 ant species in several oil palm plantation lands adjacent to natural habitats. According to Yulminarti et al (2012) found 53 species from 316 individuals in peat swamp forest, while the one-year-old palm oil plantation found 24 species from 237 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of ant communities in peatland planted with oil palm and adjacent natural habitat have been reported (Lucey et al 2014;Darmi et al 2015;Wang and Foster 2015;Rizali et al 2020). Previous research conducted by Darmi et al (2015) compared the differences of ant communities in the oil palm stands with different ages.…”
Section: Introductionmentioning
confidence: 99%